2001
DOI: 10.1093/jn/131.3.972s
|View full text |Cite
|
Sign up to set email alerts
|

Nα-(1-Deoxy-D-fructos-1-yl)-L-Arginine, an Antioxidant Compound Identified in Aged Garlic Extract

Abstract: Aged garlic extract (AGE) has been shown to have antioxidant activity. The organosulfur compounds, S-allyl-L-cysteine and S-allylmercapto-L-cysteine, are responsible, at least in part, for the antioxidant activity of AGE. To identify major active components, we fractionated AGE, using hydrogen peroxide scavenging activity as an antioxidative index. Strong activity in the amino acid fraction was found and the major active compound was identified as N alpha-(1-deoxy-D-fructos-1-yl)-L-arginine (Fru-Arg). Antioxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
86
0
3

Year Published

2002
2002
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(92 citation statements)
references
References 13 publications
3
86
0
3
Order By: Relevance
“…[1][2][3][4][5][6] On the other hand, other compounds such as saponins, proteins or maillard reaction products derived from garlic, which are non-sulfur containing compounds, have also been investigated to reveal the biological properties of garlic. 1,2,[7][8][9][10] Allixin (3-hydroxy-5-methoxy-6-methyl-2-penthyl-4H-pyran-4-one), a non-sulfur containing compound having a gpyrone skeleton structure (Fig. 1), was the first compound isolated from garlic as a phytoalexin, a product induced in plants by continuous stress.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6] On the other hand, other compounds such as saponins, proteins or maillard reaction products derived from garlic, which are non-sulfur containing compounds, have also been investigated to reveal the biological properties of garlic. 1,2,[7][8][9][10] Allixin (3-hydroxy-5-methoxy-6-methyl-2-penthyl-4H-pyran-4-one), a non-sulfur containing compound having a gpyrone skeleton structure (Fig. 1), was the first compound isolated from garlic as a phytoalexin, a product induced in plants by continuous stress.…”
mentioning
confidence: 99%
“…1,2,[7][8][9][10] Allixin (3-hydroxy-5-methoxy-6-methyl-2-penthyl-4H-pyran-4-one), a non-sulfur containing compound having a gpyrone skeleton structure ( Fig. 1), was the first compound isolated from garlic as a phytoalexin, a product induced in plants by continuous stress.…”
mentioning
confidence: 99%
“…Katsuki et al (2006) reported an inhibitory effect of SAC observed in a DMH-induced colorectal carcinogenesis experiment using mice. Garlic smell derived from sulfide components was reduced by autoclave treatment in HTPG, and the color of the powder became brown due to the Maillard reaction, suggesting that HTPG is similar to aged garlic extract (prepared by long-term aging of sliced raw garlic in alcoholic water (Amagase, 2006)) and fermented garlic (or black garlic) (Sato et al, 2006a;Sasaki et al, 2007;Wang et al, 2010), and contains S-allylmercaptocysteine, fructosyl arginine, and tetrahydro-β-carboline derivative, in addition to SAC (Imai et al, 1994;Ryu et al, 2001;Ichikawa et al, 2006;Sato et al, 2006b). A Korean research group which initially reported the HTPG production method identified an antioxidative substance, thiacremonone (Hwang et al, 2007), and showed that this substance alone exhibited an anticancer effect on human colon cancer cells and strengthened the growth inhibition effect of chemotherapeutic drugs (Ban et al, 2007;Ban et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…We prepared high-temperature and pressure-treated garlic (HTPG) using a simple autoclave and attempted measurement of antioxidative activity and total polyphenol, and observed that antioxidative activity was enhanced and total polyphenol levels were 25 times higher (Tomatsu et al, 2007). This was not due to generation of sulfur compounds of the sulfide system by the garlic-specific alliin-alliinase system, but it may have been due to changes in sulfide and non-sulfide components (e.g., γ-glutamyl-S-allylcysteine and fructan) originally having weak physiological activity to an extract with a strong antioxidative activity by hightemperature and pressure (Ryu et al, 2001;Amagase, 2006;Ichikawa et al, 2006). Thus, we firstly investigated the influences of HTPG on MDF and ACF formation in DMH-induced colorectal precancerous lesions and DMH-induced O 6 -methylguanine (O 6 -MeG) DNA adduct formation in colorectal mucosae and livers in rats.…”
Section: Introductionmentioning
confidence: 99%
“…Sedangkan pada preeklampsi, terjadi stress oksidatif yang mengakibatkan terjadinya perubahan kearah prokoagulan sehingga akan terjadi peningkatan konsumsi trombosit yang berakibat penurunan jumlah trombosit (13,14,15).…”
Section: Diskusiunclassified